2020
DOI: 10.1186/s12909-020-02033-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between learning environment variables and students’ approaches to studying: a cross-sectional study

Abstract: Background: Aspects of the learning environment may be related to students`approaches to studying, but few studies have investigated these relationships in the context of occupational therapy education. Objective: To examine associations between occupational therapy students' perceptions of the learning environment and their approaches to studying. Method: One hundred eighty-seven first-year occupational therapy students in Norway (response rate 61.3%) participated in this study. Aside from sociodemographic in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 37 publications
5
31
0
Order By: Relevance
“…The high participation rate in the study may also be attributed to study goals being highly related to course goals, thus increasing relevance and meaning of study participation for the students. To understand the purpose and relevance of course work correlates with increased engagement academically [ 31 , 32 ] therefore it seems reasonable that student participation in study procedures could have been enhanced by these factors.…”
Section: Discussionmentioning
confidence: 99%
“…The high participation rate in the study may also be attributed to study goals being highly related to course goals, thus increasing relevance and meaning of study participation for the students. To understand the purpose and relevance of course work correlates with increased engagement academically [ 31 , 32 ] therefore it seems reasonable that student participation in study procedures could have been enhanced by these factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of this study should not be interpreted as evidence of the learning environment being irrelevant. In fact, studies have demonstrated associations between learning environment factors and students' use of study approaches [24][25][26][27][28]33], suggesting that learning environment factors may in uence academic performance indirectly by in uencing study behaviors. In addition, their relationship to students' satisfaction with courses and study programs [20,22] and students' well-being [23] strongly suggest that they are important for several good reasons.…”
Section: Discussionmentioning
confidence: 99%
“…For example, direct associations between learning environment variables and academic grades were non-existing in a Norwegian study of higher education students [1]. On the other hand, studies from various disciplines, including occupational therapy, have consistently demonstrated associations between learning environment factors and students' approaches to studying [24][25][26][27][28][29]. For instance,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some sociodemographic factors – in particular higher age and female gender – have been found to contribute to determine their academic performance [ 5 , 6 ]. In recent studies of occupational therapy students, having the current study program listed as the prioritized line of education at the time of enrolment has been shown to be associated with study behaviors [ 7 , 8 ]. Moreover, having prior experience from higher education and spending more time on independent self-study has been shown to be associated with study behaviors [ 8 , 9 ] and academic achievements [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%